Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.9734/jpri/2019/v28i330203
|View full text |Cite
|
Sign up to set email alerts
|

An Overview on Common Organic Solvents and Their Toxicity

Abstract: Organic solvents are known as carbon-based solvents and their general property is primarily based on their volatility, boiling point, the molecular weight and color. Having enormous hazards associated with the organic solvents, they are used for millions of purposes which alert us to think more on its toxicity points. Almost all of the solvents are hazardous to health, if swallowed or inhaled more than the limit quantity and on contact to the skin most of them cause irritation. Some of the common solvents are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
156
0
16

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 359 publications
(200 citation statements)
references
References 100 publications
(99 reference statements)
0
156
0
16
Order By: Relevance
“…For yeast cells, however chloroform-methanol extraction is still the most common method even though ÈertĂ­k et al (1996) already showed that EH is also suitable for Mucor mucedo. In contrast to chloroform, hexane is non-carcinogenic but still neurotoxic (Joshi and Adhikari, 2019). After all, there is no alternative to hexane in lipid extraction (Breil et al, 2016).…”
Section: Influence Of Solvents On Extraction Yieldsmentioning
confidence: 99%
“…For yeast cells, however chloroform-methanol extraction is still the most common method even though ÈertĂ­k et al (1996) already showed that EH is also suitable for Mucor mucedo. In contrast to chloroform, hexane is non-carcinogenic but still neurotoxic (Joshi and Adhikari, 2019). After all, there is no alternative to hexane in lipid extraction (Breil et al, 2016).…”
Section: Influence Of Solvents On Extraction Yieldsmentioning
confidence: 99%
“…Therefore, the results in Table 1 can be explained considering that in the present work acetone, which was used as a cosolvent, probably reduced the thermal stability of A. oryzae β-galactosidase. Despite this disadvantage of using acetone as a co-solvent, it is worth mentioning that acetone also has desirable properties: it is miscible with water, it is an aprotic solvent that cannot act as an acceptor in transgalactosylation reactions, whereby unwanted parallel reactions are avoided, it can be produced from renewable raw materials, and it is generally classified as a green solvent ( Joshi and Adhikari, 2019 ). In addition, the adverse effect of acetone on enzyme stability decreases significantly at 30°C.…”
Section: Resultsmentioning
confidence: 99%
“…These solvents are labeled as "recommended" or "preferred" in several guidelines, such as the GlaxoSmithKline (GSK) [86], Pfizer [87] Sanofi [88], AstraZeneca, and Green Chemistry Institute-Pharmaceutical Roundtable (GCI-PR) solvent guidelines. These guides deal with solvents from the safety, occupational health, environment, technical constraint, and cost perspectives [89].…”
Section: Non-conventional Solvent Extractionmentioning
confidence: 99%